Rotational Grazing System for Beef Cows on Dwarf Elephantgrass Pasture for Two Years after Establishment - Mukhtar, M; Ishii, Y (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
An intensive rotational grazing system for dwarf and late heading (DL) elephant grass (Pennisetum purpureum Schumach) pasture was examined in a summer period for two years following establishment. Four 0.05 of DL elephant grass pastures (20Ã25 m) were established on May 2003. They were rotationally grazed for 1 week, followed by a 3-week rest period by three breeding or raising beef cattle for three and six cycles during the first and second years of establishment respectively. Before grazing, the plant height, leaf area index and the ratio of leaf blade to stem were at the highest, while tiller number increased and herbage mass tended to increase, except for the first grazing cycle both two years and for one paddock in the second year. Herbage consumption, the rate of herbage consumption and dry matter intake tended to decrease in three paddocks from the first to the third cycle in the first year, but increase as grazing occurred in the second year. Dry matter intake averaged 10.2-14.5 and 15.4â23.2 g DM/kg/live weight (LW)/day over the four paddocks in the first and second year, respectively, and average daily gains were 0.09 and 0.35 kg/head/day in the first and second year respectively. The carrying capacities were estimated at 1,016 and 208 cow-days (CD)/ha (annual total 1,224 CD/ha) in the first year and 1,355 and 207 CD/ha (annual total 1,562 CD/ha) in the second year. Thus, DL elephant grass pasture can expand the grazing period for beef cows for the following two-year establishment. (Animal Production 13(1):10-17 (2011)Â Key Words: dwarf elephant grass, herbage mass, plant characters, rotational grazing